Content validity of manual spinal palpatory exams - A systematic review - Reinsch Sibylle; Adams Alan; Dickerson Vivian M; Mishra Shiraz I; Seffinger Michael A; Najm Wadie I; Murphy Linda S; Goodman Arnold F (BMC Complementary and Alternative Medicine, 2003)
Abstract Background Many health care professionals use spinal palpatory exams as a primary and well-accepted part of the evaluation of spinal pathology. However, few studies have explored the validity of spinal palpatory exams. To evaluate the status of the current scientific evidence, we conducted a systematic review to assess the content validity of spinal palpatory tests used to identify spinal neuro-musculoskeletal dysfunction. Methods Review of eleven databases and a hand search of peer-reviewed literature, published between 1965–2002, was undertaken. Two blinded reviewers abstracted pertinent data from the retrieved papers, using a specially developed quality-scoring instrument. Five papers met the inclusion/exclusion criteria. Results Three of the five papers included in the review explored the content validity of motion tests. Two of these papers focused on identifying the level of fixation (decreased mobility) and one focused on range of motion. All three studies used a mechanical model as a reference standard. Two of the five papers included in the review explored the validity of pain assessment using the visual analogue scale or the subjects' own report as reference standards. Overall the sensitivity of studies looking at range of motion tests and pain varied greatly. Poor sensitivity was reported for range of motion studies regardless of the examiner's experience. A slightly better sensitivity (82%) was reported in one study that examined cervical pain. Conclusions The lack of acceptable reference standards may have contributed to the weak sensitivity findings. Given the importance of spinal palpatory tests as part of the spinal evaluation and treatment plan, effort is required by all involved disciplines to create well-designed and implemented studies in this area.